THE ERA OF CONNECTIVITY: THE ROLE OF EDUCATION IN SHAPING ADAPTIVE DIGITAL INTELLIGENCE - Roby Ahada; Najamuddin Petta Solong; Novia Nelza; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
The era of growing connectivity demands the role of education in shaping adaptive digital intelligence for students. This research uses the literature method to find findings on the role of education in shaping adaptive digital intelligence. The findings show the importance of education in helping students develop adaptability, creativity and critical thinking skills in the face of technological change. The integration of technology into the education curriculum is necessary to facilitate learning that supports the development of adaptive digital intelligence. In addition, the role of educators in integrating adaptive digital intelligence into daily learning practices includes guiding students in the effective use of technology, facilitating collaborative learning, and providing challenges in a digital context. The importance of creating a learning environment that supports adaptive digital intelligence is also an important finding in this study. Adequate technology facilities, collaboration between students in technology exploration, and support for experimentation and innovation are important factors in helping students face the era of connectivity. However, this study also provides an important note about expanding digital literacy to deal with digital risks such as cyberbullying and digital injustice.